Buried secrets : truth and human rights in Guatemala - Sanford, Victoria (New York : Palgrave Macmillan, 2004)
Between the late 1970s and the late 1980s, Guatemala was torn by mass terror and extreme violence in a genocidal campaign against the Maya, which becameknown as "La Violencia." More than 600 massacres occurred, one and a half million people were displaced, and more than 200,000 civilians were murdered, most of them Maya. Buried Secrets brings these chilling statistics to life as it chronicles the journey of Maya survivors seeking truth, justice, and community healing, and demonstrates that the Guatemalan army carried out a systematic and intentional genocide against the Maya. The book is based on exhaustive research, including more than 400 testimonies from massacre survivors, interviews with members of the forensic team, human rights leaders, high-ranking military officers, guerrilla combatants, and government officials. Buried Secrets traces truth-telling and political change from isolated Maya villages to national political events, and provides a unique look into the experiences of Maya survivors as they struggle to rebuild their communities and lives.
"The bones don't lie" -- The silencing of Maya women -- "It fills my heart with sadness" : ethnography of genocide part 1 -- The exhumation and the anti-Christ : ethnography of genocide part 2 -- The phenomenology of terror -- Guatemalan army campaigns of genocide -- From survivor testimonies to the discourse of power -- The power effects of declaring the truth -- Excavations of the heart : healing fragmented communities -- Genocide and the "grey zone" of justice.
Includes bibliographical references and index.
Keywords: Mayas -- Crimes against -- Guatemala; Human rights -- Guatemala; Mayas -- Guatemala -- Government relations; Political violence -- Guatemala; Genocide -- Guatemala